Management of type 2 Diabetes in patients with Chronic Kidney Disease - Beena Bansal; Jitender Chauhan (Archives of Clinical Nephrology - Peertechz Publications, 2017)
About 30-40% of patients with chronic kidney disease (CKD) patients also have concomitant diabetes (1). Diabetes has been shown to have signifi cantly stronger association with CKD in patients with younger age (2). Diabetes management in CKD poses signifi cant challenge because of the increased risk of hypoglycaemia, renal excretion of most oral antidiabetics, variable appetite of patients with CKD and the effects of hemodialysis and peritoneal dialysis on glycemic control. Management of diabetes after renal transplantation is a separate entity with different challenges due to the effect of immunosuppressants especially steroids on carbohydrate metabolism and will not be discussed in this review.